Elements of managing transfer of technology from laboratory to industry: technology transfer management (TTM) - Saraf, C. U. (Journal of Scientific & Industrial Research, 2014)
This research paper throws light on problems faced by small, medium and large scale. chemical industries in managing the transfer of technology from laboratory to industry. There are several reasons that may increase cost and time overruns and thus causes inordinate delay in completing transfer of technology in both private and public sector projects. This paper also suggests solutions to eliminate the problems and underlines the importance of involving local and national R & D institutes in effectively ``Managing Transfer of Chemical Technology'' into commercial practice. This communication presents ``a13 steps model'' developed by the researcher for efficient, smooth and effective transfer of technology. The findings have been duly supported by data interpretations, with appropriate examples of technology transfer and literature published. The primary data collection technique used is structured questionnaire as well as in-depth interviews of entrepreneurs, heads of R and D units and staff involved in technology transfer in chemical industries in and around Pane. The facts are also supported by the secondary analysis of literature published in related area. The basic objective of this communication is to communicate Technology Transfer Process Model (TTP) for effective commercialization of technology.
Keywords: Industrial Technology Commercialization; Multi Disciplinary Man Power Team (MDMPT); Technology Management; Technology Transfer; Technology Transfer Offices (TTO); Technology Transfer Process Model (TTP)